2021
DOI: 10.3390/plants10040613
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of dsRNA Targeting the Pentalonia nigronervosa acetylcholinesterase Gene in Banana and Plantain Reduces Aphid Populations

Abstract: The banana aphid, Pentalonia nigronervosa, is the sole insect vector of banana bunchy top virus (BBTV), the causal agent of banana bunchy top disease. The aphid acquires and transmits BBTV while feeding on infected banana plants. RNA interference (RNAi) enables the generation of pest and disease-resistant crops; however, its effectiveness relies on the identification of pivotal gene sequences to target and silence. Acetylcholinesterase (AChE) is an essential enzyme responsible for the hydrolytic metabolism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Based on research, banana cultivars that have AA and AB genomes were most favored by P. nigronervosa [25]. In transmitting banana dwarf disease, P. nigronervosa secretes viruses inhaled simultaneously with infected fluids when this insect feeds [20]. Viruses inhaled by P. nigronervosa enter the gut of the insect.…”
Section: Discussionmentioning
confidence: 99%
“…Based on research, banana cultivars that have AA and AB genomes were most favored by P. nigronervosa [25]. In transmitting banana dwarf disease, P. nigronervosa secretes viruses inhaled simultaneously with infected fluids when this insect feeds [20]. Viruses inhaled by P. nigronervosa enter the gut of the insect.…”
Section: Discussionmentioning
confidence: 99%
“…Although dsRNA derivatives are synthesized in cytoplasm and aphids are phloem feeders, and we have not found direct proof for dsRNA transmission from cytoplasm to phloem in plants, the following facts indicate its possibility. Many reports have shown that the dsRNA synthesized by transgenic crops is efficient at triggering RNAi in phloem feeder pests 72–75 . This might indicate that there is sufficient dsRNA transmitted from plant cells to phloem to dose these pests.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that the dsRNA synthesized by transgenic crops is efficient at triggering RNAi in phloem feeder pests. [72][73][74][75] This might indicate that there is sufficient dsRNA transmitted from plant cells to phloem to dose these pests. In addition, the mRNAs of host plants (cucumbers) have been detected in a phloem feeder (green peach aphid) feeding on them, which proves that the mRNA synthesized in plant cells could transmit to phloem.…”
Section: Discussionmentioning
confidence: 99%
“…The banana aphid, Pentalonia nigronervosa , is the sole insect vector of banana bunchy top virus, the causal agent of banana bunchy top disease. RNAi in P. nigronervosa , resulted in increased insect mortality by targeting the acetylcholinesterase (AChE) gene for silencing through transgenic expression of AChE dsRNA in banana and plantain plants (Jekayinoluwa et al, 2021). AChE is an essential enzyme responsible for the hydrolytic metabolism of the neurotransmitter acetylcholine in animals.…”
Section: Rnai For Control Of Hemipteran Pestsmentioning
confidence: 99%